2020
DOI: 10.22541/au.158981291.19939657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vitamin D Supplementation Could Potentially Reduce Risk of COVID-19 Infections and Deaths

Abstract: Vitamin D has long been known to be a major regulator for both the endocrine and the immune system. With the advent of COVID-19 pandemic, there has been a growing interest in looking at the feasibility of using vitamin D as a preventative and therapeutic option in the management of the disease. A low serum level of vitamin D is linked to higher incidence of respiratory tract infection and disease progression. Vitamin D supplementation has proven to be effective in enhancing the immune system, strengthen lung e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Conversely, vitamin D supplements were reportedly associated with a less severe disease progress and faster recovery rates in COVID-19 patients ( C. Annweiler et al, 2020 ; G. Annweiler et al, 2020 ; Rastogi et al, 2020 ; Tan et al, 2020 , Tan et al, 2020 ). Vitamin D supplementation has recently been reviewed ( Grant et al, 2020 ; Malek Mahdavi, 2020 ; Tay, Mahajan, & Thornton, 2020 ) with the conclusion that it is effective in boosting the immune system, strengthening the lung epithelial barrier, and preventing an excessive inflammatory response and viral infections.…”
Section: Vitamins and Ace2mentioning
confidence: 99%
“…Conversely, vitamin D supplements were reportedly associated with a less severe disease progress and faster recovery rates in COVID-19 patients ( C. Annweiler et al, 2020 ; G. Annweiler et al, 2020 ; Rastogi et al, 2020 ; Tan et al, 2020 , Tan et al, 2020 ). Vitamin D supplementation has recently been reviewed ( Grant et al, 2020 ; Malek Mahdavi, 2020 ; Tay, Mahajan, & Thornton, 2020 ) with the conclusion that it is effective in boosting the immune system, strengthening the lung epithelial barrier, and preventing an excessive inflammatory response and viral infections.…”
Section: Vitamins and Ace2mentioning
confidence: 99%
“…Black churches routinely deal with a mistrust of medical professionals perpetuated through the collective memory of the Tuskegee Syphilis Experiment. 50,51 Pew Research data indicated that Blacks were more skeptical than other groups about trusting medical professionals, and they questioned the safety and effectiveness of COVID-19 vaccines. 52,53 The high rate of COVID-19 deaths among Blacks and the need for minorities in clinical trials for COVID-19 vaccines perpetuated this skepticism about medical expertise with claims that the pandemic was a deliberate plot against minorities.…”
Section: Introductionmentioning
confidence: 99%